Modelling the variability of brain structures, activation, and connectivity - Juan, Zhou (2008)
This thesis focus on modelling the variability of brain structures, activation, and connectivity using fuzzy templates based segmentation, fuzzy modelling and clustering with contextual constraints, and dynamic Bayesian networks, respectively.